Pengembangan Produk Pariwisata Melalui Pemasaran Digital UMKM Desa Wisata Tipang Kab. Humbang Hasundutan - Ellyta Elfrida Tambunan (Politeknik Pariwisata Medan, 2022)
This research is motivated by the problems currently being faced by the COVID-19 pandemic which until now has greatly impacted the sustainability of business lines, companies and tourist destinations. For this reason, strategies for existence are needed to face this pandemic period. So that it encourages business people and MSME actors to use technological advances as an alternative strategy. One way is to implement a marketing strategy through digital marketing which is the best solution and way to market MSME products at Tipangg Tourism Village, Baktiraja District, Humbang Hasundutan Regency. The focus of the problem in this study is (1) How is the marketing strategy carried out by the Tipangg Tourism Village Pokdarwis in increasing the sales turnover of MSME products during the pandemic. (2) What are the obstacles experienced by the Tipangg Tourism Village Pokdarwis in carrying out marketing strategies through digital marketing (digital marketing). (3) What are the solutions carried out by the Tipangg Tourism Village Pokdarwis to overcome marketing strategy constraints through digital marketing (digital marketing).